Boosting Students' Writing Ability Through Instagram's Caption - Nina Rosiana Putri; Lulud Oktaviani (Univeristas Negeri Gorontalo, 2021)
ABSTRACT Social media is a tool used by people for communicating to each other in this millennial era. One of them is Instagram. In this pandemic era, people have changed their ways of life and communication that used more online activities. It includes education aspect which becomes online as an instruction of Ministry of Education. Thus, the role of social media is also very important in the online learning. Instagram can be one of means of teaching and learning process. It can help a learning process to build the interaction between teacher and students. So, this research was conducted to see how the implementation of Instagram on students’ writing ability and how to maintain the interactions in online learning. The qualitative method was applied to this study because the data were collected from questionnaire that were distributed through Google Form. The subject were senior high school students. To sum up, the result showed that the students’ writing ability was improved. Most of the students participated well in Instagram. Then, through Instagram, most students interacted in learning process until the end of class. So, it can be concluded that teacher can use Instagram in writing activity and build the interaction well in learning process.